Trajetória docente e campo da educação física no Instituto Federal de Educação, Ciência e Tecnologia do Ceará - Gomes, Daniel Pinto (2024)
This study analyzes the trajectory of the field of physical education at the Federal Institute of Education, Science and Technology of Ceará (IFCE), in the light of the trajectory of some of its agents. The research hypothesis is that physical education at the IFCE acquires various meanings due to the symbolic stances of its agents: a sense of sports training, academic discipline, criticism of the body culture of movement, professional training, adventure practice, etc. In this movement, the belonging of physical education agents to IFCE's teaching and/or management staff, sports associations, professional councils, course collegiate bodies, basic education and/or undergraduate curricula have a major impact on their beliefs and practices within the field. The strategies developed by its agents, teachers and other institutions involved, also allow us to identify the continuities and changes in the field of physical education at IFCE. In order to demonstrate the hypotheses, the historical processes experienced by this researcher, the author of this thesis, throughout the early years of the IFCE are described, placing it in comparison with other teaching trajectories and the trajectory of the institution's physical education field. In the analysis, the practices and beliefs surrounding physical education are related to the IFCE's internal regulation systems, identifying their modus operandi and characterizing the symbolic capitals at play in the field.